Applying Pump Affinity Laws to an Isolated Solar-Powered Pumping Station - F. Javier Martínez-Solano; Josep Francesc Pons-Ausina; Pedro L. Iglesias-Rey; Gonzalo López-Patiño (Engineering Proceedings)
Water pumping is highlighted as the major energy consumer in the water cycle. Solar energy has emerged as a promising alternative to traditional electric networks, particularly in areas lacking an electrical infrastructure. Solar-powered pumping stations are categorized as connected and isolated, with the latter adapting the pump operation based on available solar energy. This article proposes a scheme to adjust the pump operation according to natural factors, like irradiance and temperature, aiming to optimize energy use and minimize investment costs in solar panels. An application of this method in Valencia, Spain, demonstrates significant savings.